Features of the Graphic Image in the Novel Season of Migration to the North - Elrashid Yousif Mohamed Abbas (Departement of Arabic Language and Literature, IAIN Syekh Nurjati Cirebon, 2021)
This study dealt with the features of the graphic images in the novel Season of Migration to the North by the Sudanese writer Al-Tayeb Salih, in order to reveal the writer's use of the graphic image within the structure of the text of the novel. This study relied on the analytical descriptive approach, as the researcher analyzed the graphic images in the novel, such as: simile, metaphor, metaphor, and metonymy, in addition to referring to the features and purposes of these images. This study attempted to highlight the role of the Sudanese novel in enriching literary studies alongside the Arabic novel, and from what the researcher reached: the multiplicity of graphic images in the novel and its spontaneity and spontaneity, as well as the accuracy of photography that was consistent with the atmosphere of the novel, and its contribution to the interdependence of its texts, and tight coordination. The study also revealed the writer’s linguistic skill, and the depth of his experience with life that was linked to its social, political and economic context, in addition to his employment of religious and popular legacies related to people’s lives in fictional literature.تناولت هذه الدراسة ملامح الصور البيانية في رواية موسم الهجرة إلى الشمال للكاتب السوداني الطيب صالح، وذلك للكشف عن توظيف الكاتب للصورة البيانية داخل بنية نص الرواية. وقد اعتمدت هذه الدراسة على المنهج الوصفي التحليلي؛إذ قام الباحث بتحليل الصور البيانية الموجودة في الرواية مثل: التشبيه والمجاز والاستعارة والكناية، بجانب الإشارة إلى ملامح هذه الصور وأغراضها. حاولت هذه الدراسة أن تبرز دور الرواية السودانية في إثراء الدراسات الأدبية جنبًا إلى جنب مع الرواية العربية، ومما توصل إليه الباحث: تعدد الصور البيانية في الرواية وتميزها بالعفوية، والتلقائية فضلاً عن دقة التصوير الذي اتسق مع جو الرواية، وإسهامه في ترابط نصوصها، وإحكام تنسيقها. كما كشفت الدراسة عن مهارة الكاتب اللغوية، وعمق تجربته بالحياة التي ارتبطت بسياقها الاجتماعي والسياسي والاقتصادي، بجانب توظيفه للموروثات الدينية والشعبية المرتبطة بحياة النَّاس في الأدب الروائي، وكذلك أبانت الدراسة عمق ارتباط الكاتب ببيئه الريفية التي نشأ في ربوعها، ذلك الارتباط الذي أثر في مضمون الرواية موضوع البحث.